Summer upwelling frequency along the western Cantabrian coast from 1967 to 2007 - Alvarez, I. (2020)
Upwelling events have been analyzed along the western part of the Cantabrian coast from 1967 to 2007. This analysis shows that the highest number of days under upwelling favorable conditions was observed from June to September (12–14 days per month) with a probability of finding consecutive days under upwelling favorable conditions decreasing from 47% to 17% when events between 1 and 5 consecutive days were considered respectively. This situation was also corroborated by Sea Surface Temperature data which revealed the presence of cold water over the continental shelf, near coast, associated with upwelling favorable winds. This cold water was also observed inside the estuaries located in this area. The water temperature signal measured at the inner part of the Ria de O Barqueiro (NW Iberian Peninsula) from June to September 2008 showed to be negatively correlated with the Upwelling Index calculated in front of the northern Galician coast. This correlation tends to increase as the number of lag days between both variables increases. The maximum value of − 0.8 corresponds to a lag of 5 days.